Jenis-Jenis Utang Pajak dan Konsekuensinya bagi Wajib Pajak - Bemby Navita; Rosita Adelia Putri; Nabila Raihana (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Compliance in paying taxes is a crucial element in maintaining the stability and sustainability of state revenues. Taxes as the main source of state financing require active participation from every Taxpayer in fulfilling their obligations. However, in practice, there are still many Taxpayers who experience obstacles in fulfilling these obligations, resulting in tax debt. This article aims to identify the types of tax debts that commonly occur in Indonesia and to analyze the legal and administrative consequences that can arise due to negligence or non-compliance in implementing tax obligations. This study uses a qualitative descriptive approach, by describing in detail the factual conditions based on secondary data and literature reviews. The results of the study indicate that tax debts can arise in various forms, including underpayment, late payment, or debts arising from audit results. The consequences faced by Taxpayers due to tax debts can be in the form of administrative sanctions such as interest, fines, and increases, as well as potential criminal sanctions if elements of intent or tax crimes are found. The conclusion of this article emphasizes the importance of understanding, awareness, and compliance of Taxpayers to avoid legal risks and financial burdens due to tax debts. The recommendations provided include the need to improve tax education for Taxpayers and optimize the role of tax authorities in providing guidance, supervision, and law enforcement proportionally.